Spectroscopic (FT-IR, Raman, NMR) and DFT Quantum Chemical Studies on Phenoxyacetic Acid and Its Sodium Salt. Issue 5 (11th July 2012) - Samsonowicz Samsonowicz, M. M.; Regulska Regulska, E. E.; Lewandowski Lewandowski, W. W.
Abstract : FT-IR, Raman, and NMR spectra of phenoxyacetic acid and its sodium salt were recorded and analyzed. Optimized geometrical structures of studied compounds were calculated by B3LYP/6-311++G * * method. The atomic charges were calculated by Mulliken, NPA (natural population analysis), APT (atomic polar tensor), MK (Merz-Singh-Kollman method), and ChelpG (charges from electrostatic potentials using grid-based method) methods. Geometric as well as magnetic aromaticity indices, dipole moments, and energies were also calculated. The theoretical wavenumbers and intensities of IR spectra as well as chemical shifts in H 1 and C 13 NMR spectra were obtained. The calculated parameters were compared with experimental characteristics of these molecules.